Revalidation of Chusquea argentina (Poaceae, Bambusoideae, Bambuseae) on the basis of morphological, anatomical and phenological characters - Guerreiro, Carolina; Rúgolo De Agrasar, Zulma (Phytotaxa, 2014)
Chusquea (Poaceae, Bambusoideae, Bambuseae) is the most diverse genus of woody bamboos in the world. In Andean Patagonian forests of southern Argentina and Chile, several species of Chusquea are the dominant components of the understory. Chusquea argentina and C. culeou fo. longiramea were described from that area on the basis of morphological characters. Some authors have considered C. argentina to be a valid species and others have treated this and C. culeou fo. longiramea as synonyms of C. culeou. This study contributes to the delimitation of these taxa. Based on morphology and anatomy, we clarify differential characters between C. culeou and C. argentina and restore the latter as a valid species. Chusquea culeou fo. longiramea is synonymized under C. argentina. According to data of mass flowering events recorded in southern Argentina and Chile, C. culeou and C. argentina become reproductive at different times. Anatomical descriptions of culm and foliage leaf blade epidermis and cross sections are provided for each species. Comparative tables based on diagnostic characters are also included.